Growth of Immature Embryos on Different Media - Zeynep Özdemir Eroğlu (Journal of Agricultural Sciences)
Embryo culture is a method used to improve seed germination of early maturing peach and nectarine cultivars which have short fruit development period (<100-120 days). In these varieties the embryos generally are not mature by the time the fruit matures, therefore immature embryos do not germinate after regular strafication procedures. Thus, when early maturing cultivars are used as seed parent in breeding programs, the immature embryos are needed to germinate at in vitro conditions. In this study, the effects of embryo rescue media of Murashige & Skoog(MS), ½ MS and Woody-Plant Medium (WPM) supplemented with plant growth regulators (BA, IBA, IAA, GA3) on germination of immature embryos from fruits of ‘Spring Lady’ x ‘Silver King’ hybrids were investigated. There were no significant differences for embryo germination among the media, however differences for seedling height, leaf number, lateral root number and length were observed. Increased levels of BA resulted in increased the germination rate. Seedling development was better on WPM + 0.5 mg L-1 BA + 0.1 mg L-1 GA3 than the othermedia. While 40.8-71.1% of cultured immature embryos gave seedlings, survival ratio of the seedlings after growing in greenhouse for 2 months were between 8% and 38% depending on the media.